Integrasi Hukum Perlindungan Konsumen dan Persaingan Usaha Atas Data Pribadi Konsumen Pada Platform Digital - Kurnia Ambar Sari (LPPM Universitas Ekasakti Padang, 2023)
The era of the digital economy has brought convenience to consumers and has provided threats to the protection of personal data for consumers. Furthermore, data, which is currently considered as an asset, has become an important commodity for business actors to expand their market share through efforts in order to understand consumer behavior through big data. As a result, business actors are not only obliged to maintain the protection of consumers' personal data vertically, but they also should pay attention to their competitive behavior in the market horizontally with other business actors which could potentially violate consumer rights. By using a doctrinal research method which conducted a study of statutory regulations, it shows that regulations regards to the protection of personal data in the fields of consumer protection law, electronic transaction law, and personal data protection law are quite comprehensive and they accommodate consumers' privacy rights over their personal data. However, in order to prevent the concentration of market power in companies which control big data due to corporate actions and in order to increase the protection of consumers' personal data more optimally, integration between business competition authorities, consumer protection and personal data protection is needed.